Synthesis of porphyryl boronates with (un)saturated side-chains - SENGE, MATHIAS; SERGEEVA, NATALIA (My University, 2008)
Porphyrins with (un)saturated side?chains containing boron residues were developed as synthons for porphyrin functionalization. Porphyrins with mono and bis-substituted unsaturated boronyl residues were prepared in good yields (52?66 %) using a cross?metathesis approach in the presence of Grubbs I-generation catalysts. In all cases complete E?stereoselectivity (100 %) was observed. Furthermore, formal cross?metathesis products with ?,??unsaturated chains smoothly underwent addition with bis(pinacolato)diboron [(Me4C2O2)B?B(O2C2Me4)] to yield the corresponding saturated boron compounds in 60?70 % yields.
PUBLISHED
Keywords: Chemistry; boron